Two Siblings with the Same Severe Form of 21-Hydroxylase Deficiency But Different Growth and Menstrual Cycle Patterns - Lang-Muritano, Mariarosaria; Gerster, Karine; Sluka, Susanna; Konrad, Daniel (Frontiers in Pediatrics, 2017)
Congenital adrenal hyperplasia (CAH) is one of the most frequent autosomal recessive diseases in Europe. Treatment is a challenge for pediatric endocrinologists. Important parameters to judge the outcome are adult height and menstrual cycle. We report the follow-up from birth to adulthood of two Caucasian sisters with salt-wasting (SW) CAH due to the same mutation, homozygosity c.290-13A>G (I2 splice), in the 21-hydroxylase gene. Their adherence to treatment was excellent. Our objective was to distinguish the effects of treatment with hydrocortisone (HC) and fludrocortisone (FC) on final height (FH) from constitutional factors. The older girl (Patient 1), who showed virilised genitalia Prader scale III-IV at birth, reached FH within familial target height at 18 years (yr) of age. Menarche occurred at the age of 15. Her menstrual cycles were always irregular. Total pubertal growth was normal (29 cm). She showed a growth pattern consistent with constitutional delay. The younger sister (Patient 2) was born without masculinization of the genitalia after her mother was treated with dexamethasone starting in the fourth week of pregnancy. She reached FH at 16 yr of age. Her adult height is slightly below familial target height. Menarche occurred at the age of 12.5, followed by regular menses. Total pubertal growth was normal (21 cm). The average dose of HC from birth to FH was 16.7 mg/m2 in patient 1 and 16.8 mg/m2 in patient 2. They received FC once a day in doses from 0.05 to 0.1 mg. Under such therapy, growth velocity was normal starting from the age of 2.5 yr with an overall average of +0.2 SD in patient 1 and - 0.1 SD in patient 2, androstenedione levels were always within normal age range. Similarly, BMI and blood pressure were always normal; no acne and no hirsutism ever appeared. Conclusion: Two siblings with the same genetic form of 21-hydroxylase deficiency and excellent adherence to medication showed different growth and menstrual cycle patterns, rather related to constitutional factors than to underlying congenital adrenal hyperplasia. In addition, the second patient represents an example of successful in utero glucocorticoid treatment to prevent virilisation of the external genitalia.